Primary Squamous Cell Carcinoma of the Thyroid Gland Treated with Surgery and Concurrent Chemoradiotherapy, A Case Report - Jahan, Israt; Ali, Md Yousuf; Mostafa, Md Niaz; Tarannum, Tabia (East West Medical College Journal, 2024)
Introduction: Primary squamous cell carcinoma (PSCC) of the thyroid gland is one of the rarest types of all reported thyroid malignancies worldwide. It is very aggressive in nature and carries a poor prognosis. The surgical resection with adjuvant radiotherapy and chemotherapy is the most recommended treatment despite its poor reported outcome. Case presentation: A 56-year-old Asian man presented with non-tender swelling of the neck, Patient underwent total thyroidectomy and histopathology revealed carcinoma thyroid, squamous cell carcinoma, and all other primary squamous cell carcinoma were excluded by imaging and immunohistochemistry. The patient completed radiotherapy concurrent with chemotherapy but after one year of completion of treatment died due to local recurrence. Conclusion: PSCC of the thyroid gland is difficult to diagnose and is a great challenge for the managing team to plan for the best treatment option, due to its unfavorable rate of survival and lack of consensus management guidelines. EWMCJ Vol. 12, No. 1&2, January-July 2024: 107-110